The Self-Efficacy of Special and General Education Teachers in Implementing Inclusive Education in Greek Secondary Education - Spyridon Kazanopoulos; Eneko Tejada; Xabier Basogain (MDPI AG, 2022)
Teachers' self-efficacy is important as it affects their views on their ability to teach. In special education, self-efficacy is particularly critical because it helps teachers understand and assist students with special educational needs (SEND). The main objective of the current study was to examine special and general education teachers' self-efficacy for inclusive practices at Greek secondary education schools and how teachers' age, gender, teaching experience, and training affect their self-efficacy for inclusive practices. The current research is primary, quantitative, correlational, between and within groups, and has a non-experimental design. A sample was conducted by 265 general and special education teachers. The Teacher Efficacy for Inclusive Practices (TEIP) scale was used to measure teachers' perceived self-efficacy to implement inclusive classroom practices. Results indicated that teachers of special education presented higher efficacy in using inclusive instructions, collaborating, and dealing with disruptive behaviors. The training was considered a significant factor that affected attitudes of self-efficacy towards inclusive practices. Demographic characteristics, such as age and gender, do not seem to be significant factors in the formation of self-efficacy towards inclusive practices, while the effect of teaching experience in special education was statistically significant on all components of the self-efficacy scale.